The Information and Information Literacy Area of the Digital Teaching Competence - Moreno-Guerrero, Antonio José (2020)
Information and Communication Technologies (ICT) are an integral part of our lives. This fact is reflected in the educational system, where teachers must have acquired a series of digital skills that should be developed in students. The study tries to describe the area of digital competence, information, and information literacy in the students of the Master’s Degree in Compulsory Secondary Education, Baccalaureate, Vocational Training, and Language Teaching in the Campus of Ceuta. A quantitative method has been used; it has a descriptive scope and a non-experimental design of a longitudinal paradigm. The sample is 153 students. The instrument implemented is a questionnaire based on the Common Framework of Digital Teacher Competence of 2017, with a Likert scale of 6 points, and subdivided into three blocks: A (A1 and A2), considered as a basic level, B (B1 and B2), as an intermediate level, and C (C1 and C2), as an advanced level. The results show that future teachers have a medium level in the area of information competence and information literacy, presenting higher values in the storage and retrieval of information, data, and digital content. They also have average levels in the storage and retrieval of information, data and digital content, and lower levels in evaluating information, data, and digital content. We can conclude that training centered on developing digital teaching competencies is necessary, requiring, on the part of the competent authorities, adequate training plans.